A kind of absorbent cotton-based MoS2@C hollow fiber and its preparation method and application
By preparing the MoS2@C hollow fiber composite material on degreased cotton, the problems of narrow absorption bandwidth and weak absorption strength of existing microwave absorbing materials are solved, and the efficient microwave absorption and good corrosion resistance of the material are achieved.
Patent Information
- Application Number
- CN202410932660.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The existing microwave absorbing materials have the disadvantages of narrow absorption bandwidth, weak absorption strength and large density, which limit their application in 5G communication and integrated electronic devices.
Through the hydrothermal-carbonization strategy, degreased cotton is used as the precursor to realize the preparation of MoS2@C hollow fiber composite material, and the carbonization temperature is regulated to optimize the electromagnetic parameters of the material.
It achieves excellent dielectric loss and electromagnetic wave attenuation capabilities of the material, improves microwave absorption performance, and has good acid and alkali corrosion resistance and radar scattering cross-sectional performance.
Smart Images

Figure CN118727200B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorber composite materials, and specifically relates to an absorbent cotton-based MoS2@C hollow fiber and a preparation method and application thereof. Background Art
[0002] With the rapid development of information technology, the emergence of signal base stations, household appliances and wearable electronic devices has facilitated people's daily lives. At the same time, problems such as electromagnetic interference and information leakage are becoming increasingly serious. On the one hand, a large number of studies have shown that long-term exposure to electromagnetic radiation environments will harm people's health. On the other hand, in modern warfare, reducing the propagation of electromagnetic waves is of great significance to improving the survivability of weapons and equipment. Microwave absorbing materials are functional materials that can dissipate leaked electromagnetic waves as heat or other forms of energy. They are one of the effective ways to reduce electromagnetic interference and solve electromagnetic pollution problems. With the popularization of 5G communications and integrated electronic devices, new microwave absorbing materials are gradually developing in the direction of "thin absorption thickness, light weight, high absorption efficiency, wide absorption bandwidth, low filling ratio, good flexibility and good stability". However, traditional microwave absorbing materials often have shortcomings such as narrow absorption bandwidth, weak absorption intensity and high density, which limit their further application.
[0003] Carbon materials represented by graphene and carbon nanotubes (CNTs) have attracted extensive attention in the research of lightweight microwave absorbing materials due to their low density, high conductivity and low cost. However, the synthesis cost of carbon materials such as graphene and carbon nanotubes is high and is restricted by energy-intensive processes (chemical vapor deposition, hummer method, etc.). In contrast, biomass carbon materials are renewable, eco-friendly and widely distributed. In addition, a large amount of biomass materials are neglected or incinerated, which seriously pollutes the environment. Therefore, there is great development prospect in using low-cost biomass carbon materials as raw materials to prepare environmentally friendly carbon-based microwave absorbing materials.
[0004] To this end, the present invention uses cotton as a precursor and prepares absorbent cotton-based MoS2@C hollow fiber composites through a hydrothermal-carbonization strategy, and studies the effect of carbonization temperature on the microwave absorption properties of the MoS2@C composites. Summary of the invention
[0005] The purpose of the present invention is to provide a cotton wool-based MoS2@C hollow fiber and a preparation method and application thereof. The cotton wool-based MoS2@C hollow fiber composite material is prepared by hydrothermal-carbonization with MoS2@cotton wool as a precursor; in the present invention, not only the in-situ growth of MoS2 on the cotton wool surface is achieved, but also the electromagnetic parameters of the composite material can be effectively regulated by adjusting the annealing temperature. The corrosion resistance of the material is proved by experiments, and the material can be applied in practice by simulation.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The first object of the present invention is to provide a method for preparing an absorbent cotton-based MoS2@C hollow fiber, comprising the following steps:
[0008] A soluble molybdenum source and a soluble sulfur source are dissolved in a solvent, and then the treated cotton wool is added, stirred evenly to form a mixture, and subjected to a hydrothermal reaction at 160°C to 240°C, so that the soluble molybdenum source and the soluble sulfur source react to form MoS2 and grow in situ on the surface of the cotton wool fiber. After the hydrothermal reaction, the product is washed with water and ethanol for 3-5 times, respectively, and then dried at 30°C to 60°C for 12 hours to obtain MoS2@cotton.
[0009] MoS2@cotton is carbonized at 600℃~900℃ in a mixed gas growth atmosphere of reducing atmosphere and protective atmosphere. The H and O elements in the cotton wool are reduced by the reducing gas and overflow in the form of gas, and the C element is reduced to elemental C. Since the decomposition temperature of MoS2 is as high as 1370℃, high-temperature carbonization will not affect the structure of MoS2, thereby realizing the in-situ growth of MoS2 on the surface of the cotton wool, and obtaining an cotton wool-based MoS2@C hollow fiber composite material.
[0010] Furthermore, the usage ratio of the absorbent cotton and the soluble molybdenum source is 0.2g-0.6g:1mol.
[0011] Furthermore, the usage ratio of the soluble molybdenum source, the soluble sulfur source and the solvent is 1 mol:4 mol to 6 mol:60 mL, the solvent is water or a mixture of ethanol and water, and the volume ratio of water to ethanol is 1-2:1.
[0012] Furthermore, the hydrothermal reaction time is 6 h to 24 h.
[0013] The present invention uses ammonium molybdate, thiourea and absorbent cotton as raw materials, and adopts a hydrothermal method to realize in-situ growth of MoS2 on the surface of absorbent cotton fiber under the action of high temperature and high pressure to obtain MoS2@cotton, and then uses MoS2@absorbent cotton as a precursor. The absorbent cotton has a hollow structure and a large specific surface area, which is conducive to the attachment of other components. Its unique one-dimensional fibrous structure is beneficial to cross-linking to form a three-dimensional conductive network, thereby improving dielectric loss and enhancing the attenuation ability of electromagnetic waves, thereby improving its microwave absorption performance.
[0014] Furthermore, the carbonization time is 2 hours and the heating rate is 5°C / min. The purpose of carbonization is to achieve in-situ growth of MoS2 on the surface of cotton wool, and the electromagnetic parameters of the material are effectively regulated by regulating the carbonization temperature to obtain a cotton wool-based MoS2@C hollow fiber composite material.
[0015] Furthermore, the flow rate of the mixed gas is 100 sccm to 200 sccm, the mixed gas is an argon-hydrogen mixed gas, and the volume ratio of argon to hydrogen is 90 to 95:5 to 10. In the argon-hydrogen mixed gas atmosphere, the H and O elements in the absorbent cotton are reduced by hydrogen and overflow in the form of gas, and the C element therein is reduced to single substance C.
[0016] Furthermore, the method for treating the absorbent cotton is to ultrasonically wash the absorbent cotton with water and ethanol for 3-5 times, respectively, and dry it at 30℃~60℃ for 6h~12h to obtain the treated absorbent cotton; after the hydrothermal reaction is completed, the product is washed with water and ethanol for 3-5 times, respectively, and dried at 30℃~60℃ for 6h~12h to obtain MoS2@cotton.
[0017] The second object of the present invention is to provide a cotton wool-based MoS2@C hollow fiber prepared by the above-mentioned preparation method. The cotton wool-based MoS2@C hollow fiber composite material prepared by the present invention has a unique microstructure. Thanks to the one-dimensional hollow fiber structure of biomass cotton wool, MoS2 is distributed on both the inner and outer surfaces of the cotton wool-derived C fiber. This special structure is conducive to the construction of a rich MoS2-C interface, while increasing the transmission path of electrons, bringing excellent dielectric loss to the material.
[0018] The third object of the present invention is to provide the application of the above-mentioned cotton wool-based MoS2@C hollow fiber as an absorbing material in radar scattering cross section.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention uses a soluble molybdenum source, a soluble sulfur source and cotton wool as raw materials, and adopts a hydrothermal method to achieve in-situ growth of MoS2 on the surface of cotton wool fibers under high temperature and high pressure to obtain MoS2@cotton. Then, using MoS2@cotton wool as a precursor, in an Ar / H2 mixed gas atmosphere, the H and O elements in the cotton wool are reduced and overflow in the form of gas, and the C element therein is reduced to single substance C. Since the decomposition temperature of MoS2 is as high as 1370°C, high temperature will not affect the structure of MoS2, which not only achieves the in-situ growth of MoS2 on the surface of cotton wool, but also achieves effective regulation of the electromagnetic parameters of the material by regulating the carbonization temperature, thereby obtaining a cotton wool-based MoS2@C hollow fiber composite material.
[0021] (2) Compared with other MoS2-based dielectric composites, the prepared cotton wool-based MoS2@C hollow fiber composite material provided by the present invention has a unique microstructure. Benefiting from the one-dimensional hollow fiber structure of biomass cotton wool, MoS2 is distributed on the inner and outer surfaces of the cotton wool-derived C fiber. This special structure is conducive to constructing a rich MoS2-C interface, while increasing the transmission path of electrons, bringing excellent dielectric loss to the material.
[0022] (3) In practical applications, in addition to having good microwave absorption performance, the absorber also needs to have antioxidant and acid-base resistance. The absorbent cotton-based MoS2@C hollow fiber composite material prepared by the present invention has good acid and alkali corrosion resistance. This may be due to the special microstructure of MoS2@C, which avoids direct contact between cotton-derived carbon fibers and the outside world, and the attachment of MoS2 also further increases the stability of the material skeleton.
[0023] (4) Radar Cross Section (RCS) is a key indicator in radar stealth technology, which can be used to characterize the echo intensity generated by a target under radar wave irradiation. The prepared fibrous MoS2@C composite material provided by the present invention has a small radar cross section. The radar cross section (RCS) simulation proves the feasibility of the practical application of the absorbent cotton-based MoS2@C hollow fiber composite material of the present invention, and has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The crystal structure diagrams of MoS2@C obtained in Examples 1-4 of the present invention and MoS2 in Comparative Example 1 and C-700 in Comparative Example 2 are shown, wherein: Figure 1 (a) is the XRD spectrum, (b) is the XRD spectrum of Example 1-4 at 1200 cm -1 ~1800cm -1 Raman spectra of Example 1-4 at 200 cm -1 ~600cm -1 The Raman spectrum below.
[0025] Figure 2 The XPS spectrum of MoS2@C-700 obtained in Example 2 of the present invention, wherein: Figure 2 (a) is the full spectrum, (b) is the C1s fine spectrum, (c) is the S2p fine spectrum, and (d) is the Mo 3d fine spectrum.
[0026] Figure 3 The morphology and structure diagram of MoS2@C obtained in Examples 1-4 of the present invention and the MoS2 in Comparative Example 1 and the C-700 in Comparative Example 2 are shown, wherein: Figure 3(a) and (b) are SEM images of C-700 of different sizes in Comparative Example 2, (c) and (d) are SEM images of MoS2-700 of different sizes in Comparative Example 1, (e) and (f) are SEM images of MoS2@cotton of different sizes, (g) and (h) are SEM images of MoS2@C-600 of Example 1, (i) and (l) are SEM images of MoS2@C-700 of different sizes in Example 2, (m) and (n) are SEM images of MoS2@C-800 of different sizes in Example 3, (o) and (p) are SEM images of MoS2@C-800 of different sizes in Example 3; (q) is the element distribution diagram of MoS2@C-700 in Example 2.
[0027] Figure 4 The electromagnetic parameter data diagram of MoS2@C prepared in Examples 1-4 of the present invention and MoS2 in Comparative Example 1 and C-700 in Comparative Example 2, wherein: Figure 4 (a) is a comparison chart of the real part of the dielectric constant curve; (b) is a comparison chart of the imaginary part of the dielectric constant curve; (c) is a comparison chart of the dielectric loss curve; (d) is a comparison chart of the real part of the magnetic permeability curve; (e) is a comparison chart of the imaginary part of the magnetic permeability curve; (f) is a comparison chart of the magnetic loss curve.
[0028] Figure 5 The electromagnetic wave absorption performance test diagram of MoS2@C prepared in Examples 1-4 of the present invention and Comparative Example 1 MoS2-700 and Comparative Example 2 C-700 materials, wherein: Figure 5 (a) and (b) are the three-dimensional and two-dimensional RL graphs of comparative example 1, (c) and (d) are the three-dimensional and two-dimensional RL graphs of comparative example 2, (e) and (f) are the three-dimensional and two-dimensional RL graphs of embodiment 1, (g) and (h) are the three-dimensional and two-dimensional RL graphs of embodiment 2, (i) and (j) are the three-dimensional and two-dimensional RL graphs of embodiment 3, and (k) and (l) are the three-dimensional and two-dimensional RL graphs of embodiment 4, respectively.
[0029] Figure 6 The two-dimensional impedance matching diagrams of MoS2@C obtained in Examples 1-4 of the present invention and the materials of Comparative Example 1 MoS2-700 and Comparative Example 2 C-700 are shown, wherein: Figure 6 (a) is comparative example 1, (b) is comparative example 2, (c) is example 1, (d) is example 2, (e) is example 3, and (f) is example 4.
[0030] Figure 7 This is a diagram of the attenuation constants of MoS2@C prepared in Examples 1-4 of the present invention, as well as Comparative Example 1 MoS2-700 and Comparative Example 2 C-700 materials.
[0031] Figure 8The RL curve and peak frequency of MoS2@C-700 with different thicknesses obtained in Example 2 of the present invention are plotted against the coating thickness, wherein: Figure 8 (a) is the RL curve at different thicknesses, and (b) is the relationship between the peak frequency of MoS2@C-700 and the coating thickness based on the λ / 4 theoretical simulation.
[0032] Fig. 9 The radar cross-section simulation diagram of the MoS2@C-700 and MoS2@C-800 composite materials prepared in Examples 2-3 of the present invention, wherein: Fig. 9 (a) is the RCS model diagram, (b) is PEC, (c) is MoS2@C-700, (d) is the three-dimensional RCS diagram of MoS2@C-800, (e) is the two-dimensional RCS diagram of PEC, MoS2@C-700 and MoS2@C-800, and (f) is the RCS reduction diagram of MoS2@C-700 and MoS2@C-800 after removing PEC.
[0033] Fig.10 The radar cross-section simulation three-dimensional RCS diagram and interference destructive model diagram of the MoS2@C-700 and MoS2@C-800 composite materials prepared in Examples 2-3 of the present invention, wherein: Fig.10 (a) is the three-dimensional RCS diagram of PEC and (b) MoS2@C-700 under different frequencies and angles of incident electromagnetic waves, (c) is the three-dimensional RCS diagram of MoS2@C-700 after removing PEC, (d) is PEC, (e) is the two-dimensional RCS diagram of MoS2@C-700 under different frequencies and angles of incident electromagnetic waves, (f) is the two-dimensional RCS diagram of MoS2@C-700 after removing PEC; (g) is the interference destructive model.
[0034] Fig.11 Optical photographs of MoS2@C-700 prepared in Example 2 of the present invention, immersed in 1M HCl and 1M NaOH for different time periods.
[0035] Fig.12 The morphology and structure diagram of MoS2@C-700 prepared in Example 2 of the present invention before and after immersion in 1M HCl and 1M NaOH, wherein: Fig.12 (a) and (b) are SEM images before immersion in 1M HCl and 1M NaOH, respectively, and (c) and (d) are SEM images after immersion in 1M HCl and 1M NaOH, respectively.
[0036] Fig.13 This is a crystal structure diagram of MoS2@C-700 prepared in Example 2 of the present invention before and after immersion in 1M HCl and 1M NaOH. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0039] On the one hand, the present invention provides a method for preparing an absorbent cotton-based MoS2@C hollow fiber, comprising the following steps:
[0040] The absorbent cotton is ultrasonically washed with water and ethanol for 3-5 times, respectively, and dried at 30-60°C for 6-12h to obtain the treated absorbent cotton; a soluble molybdenum source and a soluble sulfur source are dissolved in a solvent, then added to the treated absorbent cotton, stirred evenly to form a mixture, and hydrothermally reacted at 160°C-240°C, the soluble molybdenum source and the soluble sulfur source react to form MoS2 and grow in situ on the surface of the absorbent cotton fiber. After the hydrothermal reaction, the product is washed with water and ethanol for 3-5 times, respectively, and then dried at 30°C-60°C for 12h to obtain MoS2@cotton; MoS2@cotton is carbonized at 600°C-900°C in a mixed gas growth atmosphere of a reducing atmosphere and a protective atmosphere, the H and O elements in the absorbent cotton are reduced by the reducing gas and overflow in the form of gas, the C element is reduced to elemental C, and an absorbent cotton-based MoS2@C hollow fiber composite material is obtained. In the present invention, the temperature of the hydrothermal reaction can be any specific point value between 160°C and 240°C, such as 160°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, etc., and the temperature of the carbonization can be any specific point value between 600°C and 900°C, such as 600°C, 700°C, 800°C or 900°C, etc. However, it is not limited to the listed values, and other values not listed in the above numerical range are also applicable, which will not be repeated here.
[0041] In the present invention, cotton is a widely planted natural plant material with the characteristics of low price, wide source, simple post-processing and fluffy structure. With ammonium molybdate, thiourea and cotton wool as raw materials, MoS2 is grown in situ on the surface of cotton wool fiber under the action of high temperature and high pressure by hydrothermal method to obtain MoS2@cotton, and then MoS2@cotton wool is used as a precursor. The cotton wool is hollow in structure and has a large specific surface area, which is conducive to the attachment of other components. Its unique one-dimensional fibrous structure is beneficial to cross-linking to form a three-dimensional conductive network, improve dielectric loss, enhance the attenuation ability of electromagnetic waves, and then improve its microwave absorption performance. Under Ar / H2 mixed gas atmosphere, the H and O elements in the cotton wool are reduced and overflow in the form of gas, and the C element therein is reduced to single substance C. Since the decomposition temperature of MoS2 is as high as 1370℃, high temperature will not affect the structure of MoS2. It not only realizes the in-situ growth of MoS2 on the surface of cotton wool, but also realizes the effective regulation of the electromagnetic parameters of the material by regulating the carbonization temperature, thus obtaining cotton wool-based MoS2@C hollow fiber composite materials.
[0042] In a specific embodiment, the amount ratio of the absorbent cotton and the soluble molybdenum source is 0.2g-0.6g:1mol. In the present invention, the mass ratio of the absorbent cotton and the soluble molybdenum source can be any specific ratio between 0.2g and 0.6g:1mol, such as 0.2g:1mol, 0.3g:1mol, 0.4g:1mol, 0.5g:1mol or 0.6g:1mol, etc. However, it is not limited to the listed values, and other values not listed in the above numerical range are also applicable, so they will not be repeated here.
[0043] In a specific embodiment, the amount ratio of the soluble molybdenum source, the soluble sulfur source and the solvent is 1 mol: 4 mol to 6 mol: 60 mL, and the solvent is water or a mixture of ethanol and water, and the volume ratio of water to ethanol is 1 to 2: 1. In the present invention, the amount ratio of the soluble molybdenum source, the soluble sulfur source and the solvent can be any specific ratio between 1 mol: 4 mol and 6 mol: 60 mL, such as 1 mol: 4 mol: 60 mL, 1 mol: 5 mol: 60 mL or 1 mol: 6 mol: 60 mL, etc. However, it is not limited to the listed values, and other values not listed in the above numerical range are also applicable, so they will not be repeated here.
[0044] In a specific embodiment, the hydrothermal reaction time is 6h to 24h. In the present invention, the purpose of the hydrothermal reaction is to achieve in-situ growth of MoS2 on the surface of absorbent cotton fiber under the action of high temperature and high pressure to obtain MoS2@cotton. The hydrothermal reaction time can be any specific value between 6h and 24h, such as 6h, 8h, 10h, 12h, 14h, 16h, 20h or 24h. However, it is not limited to the listed values, and other values not listed in the above numerical range are also applicable, so they will not be repeated here.
[0045] In a specific embodiment, the carbonization time is 2 hours and the heating rate is 5°C / min. In the present invention, the purpose of carbonization is to achieve in-situ growth of MoS2 on the surface of cotton wool, and by regulating the carbonization temperature, effective regulation of the electromagnetic parameters of the material is achieved to obtain a cotton wool-based MoS2@C hollow fiber composite material.
[0046] In a specific embodiment, the flow rate of the mixed gas is 100 sccm to 200 sccm, the mixed gas is an argon-hydrogen mixed gas, and the volume ratio of argon to hydrogen is 90 to 95:5 to 10. In the present invention, under the atmosphere of the argon-hydrogen mixed gas, the H and O elements in the absorbent cotton are reduced by hydrogen and overflow in the form of gas, and the C element therein is reduced to single substance C.
[0047] On the other hand, the present invention provides a cotton wool-based MoS2@C hollow fiber prepared by the above-mentioned preparation method. The cotton wool-based MoS2@C hollow fiber composite material prepared by the present invention has a unique microstructure. Thanks to the one-dimensional hollow fiber structure of biomass cotton wool, MoS2 is distributed on both the inner and outer surfaces of the cotton wool-derived C fiber. This special structure is conducive to the construction of a rich MoS2-C interface, while increasing the transmission path of electrons, bringing excellent dielectric loss to the material.
[0048] In practical applications, in addition to having good microwave absorption performance, the absorber also has important antioxidant and acid and alkali resistance. The prepared absorbent cotton-based MoS2@C hollow fiber composite material was immersed in 1MHCl and 1MNaOH for 0h to 72h, respectively. The results showed that it had good acid and alkali corrosion resistance. This may be due to the special microstructure of MoS2@C, which prevents cotton-derived carbon fibers from direct contact with the outside world, and the attachment of MoS2 also further increases the stability of the material skeleton.
[0049] On the other hand, the present invention provides the application of the above-mentioned cotton wool-based MoS2@C hollow fiber as an absorbing material in radar cross section. And provides a method for establishing and simulating a radar scattering model of cotton wool-based MoS2@C hollow fiber, comprising the following steps: using CST Studio Suite 2020 to simulate the radar cross section of the microwave absorber. The simulated model is established as a double-layer structure (10×10cm 2 ), a 1.0 mm perfect conductive layer (PEC) is set at the bottom, and the surface of PEC is covered with absorbing material. The MoS2@C-PEC model plate is placed on the YOZ plane, and the electromagnetic wave propagates to the middle material surface in the ZOX plane, and theta is defined as the detection angle. All directions are open boundary conditions, simulating the radar cross section of the material when electromagnetic waves of different frequencies are incident at different angles. In the present invention, the radar cross section (RCS) is a key indicator in radar stealth technology, which can be used to characterize the echo intensity generated by the target under the irradiation of radar waves. The prepared fibrous MoS2@C composite material provided by the present invention has a smaller radar cross section, which indicates that the prepared fibrous MoS2@C composite material provided by the present invention has great application potential.
[0050] The invention is further described below through specific examples.
[0051] Example 1
[0052] A method for preparing an absorbent cotton-based MoS2@C hollow fiber comprises the following steps:
[0053] S1. Wash the absorbent cotton with deionized water and anhydrous ethanol for three times by ultrasonic wave, and dry it at 60°C for 12 hours to obtain the treated absorbent cotton;
[0054] S2, add 0.6175g ammonium molybdate and 1.332g thiourea into 60mL deionized water and stir evenly, then add 400mg treated absorbent cotton, continue stirring for 1h to obtain a mixture, transfer the mixture into a 100mL reactor, react at 180°C for 18h, after the hydrothermal reaction is completed, wash the product with deionized water and anhydrous ethanol three times respectively, and dry it in vacuum at 60°C for 12h to obtain MoS2@cotton;
[0055] S3. Take 200 mg of MoS2 sample and place it in a tubular furnace with Ar / H2 mixed gas (95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 600°C for 2 h to obtain a cotton wool-based MoS2@C hollow fiber composite material, named MoS2@C-600.
[0056] Example 2
[0057] A method for preparing an absorbent cotton-based MoS2@C hollow fiber comprises the following steps:
[0058] S1. Wash the absorbent cotton with deionized water and anhydrous ethanol for three times by ultrasonic wave, and dry it at 60°C for 12 hours to obtain the treated absorbent cotton;
[0059] S2, add 0.6175g ammonium molybdate and 1.332g thiourea into 60mL deionized water and stir evenly, then add 400mg treated absorbent cotton, continue stirring for 1h to obtain a mixture, transfer the mixture into a 100mL reactor, react at 180°C for 18h, after the hydrothermal reaction is completed, wash the product with deionized water and anhydrous ethanol three times respectively, and dry it in vacuum at 60°C for 12h to obtain MoS2@cotton;
[0060] S3. Take 200 mg of MoS2 sample and place it in a tubular furnace with Ar / H2 mixed gas (volume ratio of 95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 700°C for 2 h to obtain a cotton wool-based MoS2@C hollow fiber composite material, named MoS2@C-700.
[0061] Example 3
[0062] A method for preparing an absorbent cotton-based MoS2@C hollow fiber comprises the following steps:
[0063] S1. Wash the absorbent cotton with deionized water and anhydrous ethanol for three times by ultrasonic wave, and dry it at 60°C for 12 hours to obtain the treated absorbent cotton;
[0064] S2, add 0.6175g ammonium molybdate and 1.332g thiourea into 60mL deionized water and stir evenly, then add 400mg treated absorbent cotton, continue stirring for 1h to obtain a mixture, transfer the mixture into a 100mL reactor, react at 180°C for 18h, after the hydrothermal reaction is completed, wash the product with deionized water and anhydrous ethanol three times respectively, and dry it in vacuum at 60°C for 12h to obtain MoS2@cotton;
[0065] S3. Take 200 mg of MoS2 sample and place it in a tubular furnace with Ar / H2 mixed gas (volume ratio of 95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 800°C for 2 h to obtain a cotton wool-based MoS2@C hollow fiber composite material, named MoS2@C-800.
[0066] Example 4
[0067] A method for preparing an absorbent cotton-based MoS2@C hollow fiber comprises the following steps:
[0068] S1. Wash the absorbent cotton with deionized water and anhydrous ethanol for three times by ultrasonic wave, and dry it at 60°C for 12 hours to obtain the treated absorbent cotton;
[0069] S2, add 0.6175g ammonium molybdate and 1.332g thiourea into 60mL deionized water and stir evenly, then add 400mg treated absorbent cotton, continue stirring for 1h to obtain a mixture, transfer the mixture into a 100mL reactor, react at 180°C for 18h, after the hydrothermal reaction is completed, wash the product with deionized water and anhydrous ethanol three times respectively, and dry it in vacuum at 60°C for 12h to obtain MoS2@cotton;
[0070] S3. Take 200 mg of MoS2 sample and place it in a tubular furnace with Ar / H2 mixed gas (volume ratio of 95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 900°C for 2 h to obtain a cotton wool-based MoS2@C hollow fiber composite material, named MoS2@C-900.
[0071] Comparative Example 1
[0072] A method for preparing a MoS2 composite material comprises the following steps:
[0073] S2, add 0.6175g of ammonium molybdate and 1.332g of thiourea into 60mL of deionized water and stir to obtain a mixture, then transfer the mixture into a 100mL reactor and react at 180°C for 18h. After the hydrothermal reaction is completed, wash the product with deionized water and anhydrous ethanol three times respectively, and dry it in vacuum at 60°C for 12h to obtain MoS2;
[0074] S3. Take 200 mg of MoS2 sample and place it in a tubular furnace with Ar / H2 mixed gas (volume ratio of 95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 700°C for 2 h to obtain a MoS2@C composite material named MoS2-700.
[0075] Comparative Example 2
[0076] A method for preparing an absorbent cotton composite material comprises the following steps:
[0077] S1. Wash the absorbent cotton with deionized water and anhydrous ethanol for three times by ultrasonic wave, and dry it at 60°C for 12 hours to obtain the treated absorbent cotton;
[0078] S2. Take 200 mg of cotton sample and place it in a tubular furnace with Ar / H2 mixed gas (volume ratio of 95:5) at a flow rate of 100 sccm and a heating rate of 5°C / min. Carbonize it at 700°C for 2 hours to obtain an absorbent cotton composite material named C-700.
[0079] The absorbent cotton-based MoS2@C hollow fiber composite materials prepared in Examples 1-4 of the present invention and the composite materials prepared in Comparative Examples 1-2 were compared and studied for performance, and the specific research results are as follows:
[0080] Figure 1 The crystal structure diagrams of MoS2@C obtained in Examples 1-4 of the present invention and MoS2 in Comparative Example 1 and C-700 in Comparative Example 2 are shown, wherein: Figure 1 (a) is the XRD spectrum, and (b) is the XRD spectrum of Example 1-4 at 1200 cm -1 ~1800cm -1 Raman spectra of Example 1-4 at 200 cm -1 ~600cm -1 The Raman spectrum below. Figure 1 As shown in (a), the diffraction peaks of all annealed samples are basically consistent with those of MoS2 monomer. As the annealing temperature increases, the (002) diffraction peak of MoS2 becomes narrower, and the diffraction peak intensity corresponding to the (103) crystal plane increases. This is mainly due to the increase in annealing temperature, which makes the AB stacking of MoS2 more regular. The XRD of C-700 has a peak near 20.0°, which indicates that the carbon in the material mainly exists in the form of amorphous carbon. In order to further explore the carbon in the MoS2@C composite material, Raman characterization was performed. Figure 1 As shown in (b), 1350cm -1 and 1600cm -1 There are two obvious characteristic peaks nearby, corresponding to the D band and G band of carbon. The D band represents the defects of the carbon atom lattice, and the G band represents the sp 2 Hybridized in-plane stretching vibration. Usually we use ID / IG to evaluate the graphitization degree and carbon defects of carbon. The ID / IG of MoS2@C-600, MoS2@C-700, MoS2@C-800 and MoS2@C-900 are 0.63, 0.70, 0.81 and 0.99 respectively, indicating that with the increase of carbonization temperature, the graphitization degree of carbon in MoS2@C composite materials gradually decreases and the defects increase. Figure 1 As shown in (c), the positions are 282, 376 and 406 cm -1 The characteristic peaks correspond to the E 1g 、E 2g 1 and A1g Raman vibration mode. Located at 460cm -1 The peak is a second-order Raman scattering peak, which is consistent with the literature reports.
[0081] Figure 2 The XPS spectrum of MoS2@C-700 obtained in Example 2 of the present invention, wherein: Figure 2 (a) is the full spectrum, (b) is the C1s fine spectrum, (c) is the S2p fine spectrum, and (d) is the Mo 3d fine spectrum. Figure 2 As shown, the XPS full spectrum ( Figure 2 (a) shows the characteristic peaks of S2p, Mo 3d, C 1s, Mo 3p and O1s, indicating the presence of S, Mo, C and O elements in the MoS2@C-700 composite material. Figure 2 The characteristic peaks at 284.8eV and 285.9eV in (b) correspond to CC and COC (or C-OH), respectively. Figure 2 The characteristic peaks at 162.5 eV and 163.8 eV in (c) correspond to S 2- 2p 3 / 2 and S2p 1 / 2 . The fine spectrum of Mo ( Figure 2 The characteristic peaks at 232.9 eV and 229.7 eV in (d) belong to Mo 4+ 3D 3 / 2 and 3D 5 / 2 , the peak at 226.9 eV comes from S2s.
[0082] Figure 3 The morphology and structure diagram of MoS2@C obtained in Examples 1-4 of the present invention and the MoS2 in Comparative Example 1 and the C-700 in Comparative Example 2 are shown, wherein: Figure 3 (a) and (b) are SEM images of C-700 of different sizes in comparative example 2, (c) and (d) are SEM images of MoS2-700 of different sizes in comparative example 1, (e) and (f) are SEM images of MoS2@cotton of different sizes, (g) and (h) are SEM images of MoS2@C-600 of Example 1, (i) and (l) are SEM images of MoS2@C-700 of different sizes in Example 2, (m) and (n) are SEM images of MoS2@C-800 of different sizes in Example 3, (o) and (p) are SEM images of MoS2@C-800 of different sizes in Example 3; (q) is the element distribution diagram of MoS2@C-700 in Example 2. Figure 3 As shown in (a) and (b) in Figure 2, C-700 is a one-dimensional fibrous structure with a smooth surface. Figure 3As shown in (c) and (d) in Figure 2, MoS2 is a flower ball assembled from two-dimensional nanosheets. Figure 3 As shown in (e) and (f) in Figure 2, after hydrothermal treatment, MoS2 nanosheets grow evenly on the surface of cotton fibers. Figure 3 (g) to Figure 3 (p) in the figure is the SEM image of MoS2@C composites prepared at different carbonization temperatures. The increase of carbonization temperature does not destroy the overall structure of MoS2@C composites. With the increase of annealing temperature, the wrinkles on the surface of fibrous MoS2@C composites gradually increase and twist along the radial direction of the fibers. The element distribution of MoS2@C-700 composites is shown in Figure 2. Figure 3 As shown in (q), the MoS2@C composite material is a hollow tubular structure. This special structure effectively reduces the density of the material. By characterizing the inner and outer tube walls of the MoS2@C composite material ( Figure 3 In (k) and (l), it was found that a large number of MoS2 nanosheets were attached to the inner and outer walls of the carbon fiber, and the element distribution diagram further explained this phenomenon. This special multi-layer tubular structure increases the contact area between MoS2 and cotton-derived C fibers and promotes interfacial polarization.
[0083] 20 wt % of the samples of Examples 1-4 and Comparative Examples 1-2 were uniformly mixed with 80 wt % of paraffin wax, and their electromagnetic properties were characterized. Figure 4 The electromagnetic parameter data diagram of MoS2@C prepared in Examples 1-4 of the present invention and MoS2 in Comparative Example 1 and C-700 in Comparative Example 2, wherein: Figure 4 (a) is the comparison chart of the real part of the dielectric constant curve; (b) is the comparison chart of the imaginary part of the dielectric constant curve; (c) is the comparison chart of the dielectric loss curve; (d) is the comparison chart of the real part of the magnetic permeability curve; (e) is the comparison chart of the imaginary part of the magnetic permeability curve; (f) is the comparison chart of the magnetic loss curve. Figure 4 As shown in (a) and (b), the complex dielectric constant of MoS2-700 is the lowest, the complex dielectric constant of C-700 is significantly higher than that of MoS2, and the complex dielectric constant of MoS2@C-700 is between MoS2-700 and C-700. At the same time, the complex dielectric constant of MoS2@C composite material increases with the increase of carbonization temperature, which indicates that the dielectric properties of the material can be effectively regulated by controlling the carbonization annealing temperature. Figure 4 (d) and (e) are the complex magnetic permeabilities of the materials. As typical dielectric materials, μ′ of MoS2, C-700 and MoS2@C composite materials is close to 1 and μ″ is close to 0. The μ′ and μ″ of MoS2@C-900 have an upward and downward fluctuation at high frequency, respectively, and the corresponding ε′ and ε″ have opposite fluctuations, which may be caused by the dielectric / magnetic coupling in the material. Figure 4(c) and (f) are tanδε and tanδμ of MoS2-700, C-700 and MoS2@C composite materials, respectively. Among them, MoS2@C-600 and MoS2-700 have the lowest tanδε, while MoS2@C-700, MoS2@C-800 and MoS2@C-900 have similar tanδε, and C-700 has the highest tanδε. The tanδμ of all materials is almost close to 0, indicating that the materials are dielectric lossy absorbing materials.
[0084] Figure 5 The electromagnetic wave absorption performance test diagram of MoS2@C prepared in Examples 1-4 of the present invention and Comparative Example 1 MoS2-700 and Comparative Example 2 C-700 materials, wherein: Figure 5 (a) and (b) are the three-dimensional and two-dimensional RL graphs of Comparative Example 1, (c) and (d) are the three-dimensional and two-dimensional RL graphs of Comparative Example 2, (e) and (f) are the three-dimensional and two-dimensional RL graphs of Example 1, (g) and (h) are the three-dimensional and two-dimensional RL graphs of Example 2, (i) and (j) are the three-dimensional and two-dimensional RL graphs of Example 3, and (k) and (l) are the three-dimensional and two-dimensional RL graphs of Example 4. Figure 5 As shown, the RL of MoS2-700 min Only -2.2dB( Figure 5 (a) and (b)); C-700 at RL 2.0mm min -14.0dB, EAB 5.4GHz (11.4-16.8GHz) ( Figure 5 (c) and (d)); the RLmin of MoS2@C-600 is only -5.0dB ( Figure 5 (e) and (f)); MoS2@C-700( Figure 5 (g) and (h) have the best microwave absorption performance: RL at 2.7 mm min The EAB is -67.7dB and 6.5GHz (10.2-16.7GHz); the EAB at 2.5mm can reach 6.8GHz (11.2-18GHz), covering the entire Ku band; MoS2@C-800 ( Figure 5 In (i) and (j)), when the thickness is only 1.73 mm, RL min is -62.8dB, and the effective absorption bandwidth is 5.3GHz (12.2GHz~17.5GHz); MoS2@C-900( Figure 5 (k) and (l) in RL at 1.78 mm minThe carbonization temperature can further reduce the matching thickness of the sample and obtain excellent absorbing performance.
[0085] Figure 6 The two-dimensional impedance matching diagrams of MoS2@C obtained in Examples 1-4 of the present invention and the materials of Comparative Example 1 MoS2-700 and Comparative Example 2 C-700 are shown, wherein: Figure 6 (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, (d) is Example 2, (e) is Example 3, and (f) is Example 4. Figure 6 As shown, the Z of MoS2-700 and C-700 eff The area enclosed is the smallest, indicating that its impedance matching is poor; MoS2@C composite material is a dielectric material, so its impedance matching mainly depends on the dielectric properties. eff The enclosed area shows a trend of increasing first and then decreasing, among which MoS2@C-700 has the best impedance matching, which is due to the appropriate dielectric constant. When the temperature continues to rise, the dielectric constant of the material is too large, resulting in impedance mismatch.
[0086] Figure 7 The attenuation constant diagram of MoS2@C prepared in Examples 1-4 of the present invention and the materials of Comparative Example 1 MoS2-700 and Comparative Example 2 C-700. Figure 7 As shown in the figure, the attenuation constants of MoS2-700 and MoS2@C-600 are the smallest, indicating that they have the worst attenuation ability to the incident electromagnetic wave. C-700 has the largest attenuation constant, but due to its poor impedance, its microwave absorption performance is poor. The attenuation constants of MoS2@C-700, MoS2@C-800 and MoS2@C-900 are similar, and all show relatively excellent electromagnetic wave attenuation ability.
[0087] Figure 8 The RL curve and peak frequency of MoS2@C-700 with different thicknesses obtained in Example 2 of the present invention are plotted against the coating thickness, wherein: Figure 8 (a) is the RL curve at different thicknesses, and (b) is the relationship between the peak frequency of MoS2@C-700 and the coating thickness based on the λ / 4 theory simulation. Figure 8 As shown, the dots are measured data, and the curves are simulated data. The measured data are consistent with the simulated data, indicating that the RL of MoS2@C-700 min The corresponding thickness (t) and the frequency of the absorption peak follow the λ / 4 theory, which provides a reference for the practical application of MoS2@C composites.
[0088] The establishment and simulation of the radar scattering model of the absorbent cotton-based MoS2@C hollow fiber composite material prepared in Example 2 and Example 3 include the following steps: using CST Studio Suite 2020 to simulate the radar scattering cross section of the microwave absorber. The simulated model is established as a double-layer structure (10 cm 2 ×10cm 2 ), a 1.0mm perfect conductive layer (PEC) is set at the bottom, and a certain thickness of absorbing material is covered on the surface of the PEC. The MoS2@C-PEC model plate is placed on the YOZ plane, and the electromagnetic wave propagates to the material surface in the middle in the ZOX plane. Theta is defined as the detection angle. All directions are open boundary conditions, simulating the radar scattering cross section of the material when the electromagnetic wave in the frequency range of 10.2-16.7GHz is incident at an angle of 20-160°.
[0089] Radar Cross Section (RCS) is a key indicator in radar stealth technology. It can be used to characterize the echo intensity generated by a target under radar wave illumination. The unit of RCS is dB m 2 , which represents the decibel per square meter, decreases by 10dB m 2 This means that the echo power is reduced by 90%. The calculation of RCS is as follows:
[0090] σ(dBm 2 )=10log((4πS / λ)E s / E i |) 2
[0091] Among them, S, λ, Es, and Ei are the area of the target object simulation model, the wavelength of the electromagnetic wave, the electric field intensity of the scattered wave, and the electric field intensity of the incident wave, respectively.
[0092] CST Studio Suite 2020 is used to simulate the radar cross section of microwave absorbers. Figure 9-10 The radar cross-section simulation diagram of the MoS2@C-700 and MoS2@C-800 composite materials prepared in Examples 2-3 of the present invention, wherein: Fig. 9 (a) is the RCS model diagram, (b) is PEC, (c) is MoS2@C-700, (d) is the three-dimensional RCS diagram of MoS2@C-800, (e) is the two-dimensional RCS diagram of PEC, MoS2@C-700 and MoS2@C-800, (f) is the RCS reduction diagram of MoS2@C-700 and MoS2@C-800 after removing PEC, and (g) is the relationship between microwave absorption and RCS of MoS2@C-700 in the frequency range of 10.2GHz to 16.7GHz. Fig.10The radar cross-section simulation three-dimensional RCS diagram and interference destructive model diagram of the MoS2@C-700 and MoS2@C-800 composite materials prepared in Examples 2-3 of the present invention, wherein: Fig.10 (a) is the 3D RCS diagram of PEC and (b) MoS2@C-700 under different frequencies and angles, (c) is the 3D RCS diagram of MoS2@C-700 after PEC is removed, (d) is PEC, (e) is the 2D RCS diagram of MoS2@C-700 under different frequencies and angles, (f) is the 2D RCS diagram of MoS2@C-700 after PEC is removed; (g) is the destructive interference model. According to the commonly used metal backplane model, the simulation model is established as a double-layer structure (10 cm 2 ×10cm 2 ),like Fig. 9 As shown in (a), a 1.0 mm perfect conductive layer (PEC) is set at the bottom, and a certain thickness of absorbing material is covered on the surface of the PEC. The MoS2@C-PEC model plate is placed on the YOZ plane, and the electromagnetic wave propagates toward the middle material surface in the ZOX plane. Theta is defined as the detection angle. The boundary conditions are open in all directions, and the simulation frequency is set to 12 GHz. The CST simulation results of the PEC without the sample and the PEC coated with MoS2@C-700 and MoS2@C-800 are shown in Figure 1. Fig. 9 As shown in (b) to (d), in the range of 12 GHz and 20 to 160°, the PEC without the sample and the PEC coated with MoS2@C-700 and MoS2@C-800 show three-dimensional radar wave scattering signals of different intensities, and the scattering signal of the PEC without the sample is the largest. The simulated signal of the square plate coated with MoS2@C-700 is much smaller than that of the PEC and the square plate coated with MoS2@C-800, indicating that MoS2@C-700 has the best RCS value. When the electromagnetic wave incident angle is 79°, the RCS of the square plate coated with MoS2@C-700 is 26.9 dB m 2 In the range of 20-160°, the RCS reduction is greater than 10dB m 2 The area covers 71.4% of the total area, showing good RCS performance (such as Fig. 9 From (e) to (g) in Figure 2, the average RCS of each minimum unit at 20-160° was calculated through simulation data, and the average RCS variation curve with frequency was established, as shown in Figure 2. Fig. 9 As shown in (g), the average RCS decreases with the minimum RL minThe decrease in the microwave absorption performance of MoS2@C-700 and the average RCS curve are positively correlated. In order to explore the relationship between microwave absorption performance and RCS, the RCS data of MoS2@C-700 in the range of EAB≤-10dB (10.2GHz~16.7GHz) were simulated with 0.2GHz as the minimum unit (such as Fig.10 (a) to (f) in Figure 1), when Phi is 90° (the incident wave is incident vertically), the simulated RCS attenuation is smaller than that at other angles. This is because the reflected wave and the incident wave have a phase difference of π, resulting in destructive interference (e.g. Fig.10 In (g), as the incident angle changes, the interference between the incident wave and the reflected wave weakens, and the RCS attenuation value decreases.
[0093] In practical applications, in addition to having good microwave absorption performance, the absorbent also has important antioxidant and acid and alkali resistance. The prepared absorbent cotton-based MoS2@C hollow fiber composite material was immersed in 1M HCI and 1M NaOH for 0 h to 72 h, respectively, and the results are as follows.
[0094] Fig.11 The optical photographs of MoS2@C-700 prepared in Example 2 of the present invention after being immersed in 1M HCl and 1M NaOH for different time periods are shown. Fig.11 As shown, after soaking in acid and alkali for 72 hours respectively, the acid solution and alkali solution are still clear.
[0095] Fig.12 The morphology and structure diagram of MoS2@C-700 prepared in Example 2 of the present invention before and after immersion in 1M HCl and 1M NaOH, wherein: Fig.12 (a) and (b) are SEM images before immersion in 1M HCl and 1M NaOH, respectively, and (c) and (d) are SEM images after immersion in 1M HCl and 1M NaOH, respectively. Fig.12 As shown, after immersion in 1 M HCl and 1 M NaOH for 72 h, MoS2 adhered to the surface of cotton-derived carbon fibers, indicating that the microstructure of MoS2@C-700 was not destroyed.
[0096] Fig.13 The crystal structure diagram of MoS2@C-700 prepared in Example 2 of the present invention before and after being immersed in 1M HCl and 1M NaOH. Fig.13 As shown in the figure, the XRD of MoS2@C-700 after immersion for 72 hours is consistent with that before immersion. The above results show that MoS2@C-700 has good acid and alkali corrosion resistance. This may be due to the special microstructure of MoS2@C avoiding direct contact between cotton-derived carbon fibers and the outside world, and the attachment of MoS2 also further increases the stability of the material skeleton.
[0097] According to the above research results, the absorbent cotton-based MoS2@C hollow fiber composite material prepared by the present invention has good electromagnetic wave absorption ability within 0.1-18GHz, and also has good corrosion resistance and radar scattering cross-section performance. The process is simple and the cost is low, so it can be promoted and applied in the industrial field.
[0098] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0099] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing absorbent cotton-based MoS2@C hollow fibers, characterized in that: The following steps are involved: A soluble molybdenum source and a soluble sulfur source are dissolved in a solvent, and then the treated cotton wool is added, stirred evenly to form a mixture, and subjected to a hydrothermal reaction at 180°C for 18 hours to in-situ grow MoS2 on the surface of the cotton wool fiber to obtain MoS2@cotton; the dosage ratio of the soluble molybdenum source to the soluble sulfur source is 1 mol: 4 mol to 6 mol; the dosage ratio of the cotton wool to the soluble molybdenum source is 0.2 g to 0.6 g: 1 mol; MoS2@cotton was carbonized at 700℃~900℃ for 2h in a mixed gas growth atmosphere of reducing atmosphere and protective atmosphere, with a heating rate of 5℃ / min. The H and O elements in the absorbent cotton were reduced by the reducing gas and overflowed in the form of gas, and the C element was reduced to elemental C, thus obtaining an absorbent cotton-based MoS2@C hollow fiber composite material. The flow rate of the mixed gas is 100 sccm-200 sccm, the mixed gas is an argon-hydrogen mixed gas, and the volume ratio of argon to hydrogen is 90-95:5-10.
2. The method for preparing the absorbent cotton-based MoS2@C hollow fiber according to claim 1, characterized in that: The soluble molybdenum source is ammonium molybdate or sodium molybdate, and the soluble sulfur source is thiourea or thioacetamide.
3. The method for preparing the absorbent cotton-based MoS2@C hollow fiber according to claim 1, characterized in that: The usage ratio of the soluble molybdenum source and the solvent is 1 mol:60 mL, the solvent is water or a mixture of ethanol and water, and the volume ratio of water to ethanol is 1-2:
1.
4. A cotton-based MoS2@C hollow fiber prepared by the preparation method according to any one of claims 1 to 3.
5. An application of the absorbent cotton-based MoS2@C hollow fiber as claimed in claim 4 as an absorbing material in radar cross section.
Citation Information
Patent Citations
Molybdenum sulfide / carbon composite material and preparation method and application thereof
CN106910884A
MoS2 / carbon fiber network flexible electrode and preparation method and application thereof
CN107316979A
Dielectric fiber composite wave-absorbing material with surface coated with molybdenum disulfide / ferrocobalt alloy / carbon and preparation method thereof
CN113816620A
Electromagnetic shielding wave-absorbing material C / MoS2 as well as preparation method and application thereof
CN117691367A